Extreme Referendum: Donald Trump and the 2018 Midterm Elections - JACOBSON, GARY C. (Political science quarterly, 2019)
LONG‐TERM POLITICAL TRENDS and the public's reaction to Donald Trump's surreal presidency converged to make the 2018 midterm elections the most sweeping and discordant national referendum on any administration at least since the Great Depression. Midterms have grown increasingly nationalized, partisan, and president centered over recent decades, but Trump's persona, rhetoric, and policies extended all of these trends into uncharted territory. Trump's polarizing performance and electoral salience cost Republicans control of the House of Representatives but strengthened their grip on the Senate, setting the stage for fierce partisan battles within and between the branches during the 116th Congress. In this article, I place the 2018 referendum in historical context; examine the extraordinary influence Trump exerted on the electoral environment, strategic political choices, and voting decisions; and consider the referendum's implications for the new Congress and the future of the two parties.